As a form of 'telling': analyzing the use of hypotheticals in end-of-life (EOL) conversations through the discourse of advance care planning (ACP) discussions - Ang, Gregory Ching Hai (Nanyang Technological University, 2024)
Hypothetical is a complex interactional phenomenon that has been heavily neglected in the literature. While linguistically we understand hypotheticals to be imaginary statements/constructions that can be formed with the use of conditionals, interactionally it is much more complicated. When reviewing the scarce literature on interactional hypotheticals (or hypothetical-tellings), we see that, in structure and function, it shares some similarities with the phenomenon of storytelling. With this foundational understanding in tellings as a larger activity, we seek to understand how hypotheticals function as interactional devices and what are the affordances provided by the interactional space of these hypothetical-tellings as an activity in institutional talk. To analyze this, we observe the use of hypotheticals in End-of-Life (EOL) conversations from two cases of Advanced Care Planning (ACP) discussions from a database of 42 sessions in total. An Ethnomethodological Conversation Analysis (EMCA) perspective was applied in the analysis of this data to better understand the interactional works of hypotheticals from the talk itself. Specifically, this paper focuses on two main aspects of hypothetical-tellings: (1) the interactional space provided by hypothetical-tellings as an activity, and (2) the importance in the consideration of the epistemic paradigm of the patients and/or their Next-of-Kins (NOK). We argue that the activity of hypothetical-tellings provides the interactional space for patient resistance to be realized. This resistance then allows the clinicians to co-construct the hypotheticals with their patients and understand the epistemic paradigm of their social realities when patients are making these decisions for EOL care. We also argue that hypothetical-tellings possess certain features that allow for the teller (i.e., the clinician) to embed stance within their talk. In the multiple construction of hypotheticals within the same activity sequence, the clinician is able to construct some of these plausible future scenarios very differently from others which display certain stances. Overall, we seek to observe interactional realizations of hypothetical constructions as a possible interactional activity on its own. From that it provides the affordances for phenomena like co-construction and stance-embedding to occur. The insights from this paper also stresses the importance of the epistemic paradigm of the patient and the importance of displaying this understanding of their social realities within the talk itself in the context of ACP discussions.